Blunt traumatic thoracic aortic injuries: a retrospective cohort analysis of 2 decades of experience. (29th March 2021) - Prendes, Carlota Fernandez; Stana, Jan; Schneidwind, Karina Domingos; Rantner, Barbara; Konstantinou, Nikolaos; Bruder, Jan; Kammerlander, Christian; Banafsche, Ramin; Tsilimparis, Nikolaos
Abstract: OBJECTIVES: The aim of this study was to analyse and report the changes in the management of blunt traumatic aortic injuries (BTAIs) in a single centre during the last 2 decades. METHODS: A retrospective analysis of all patients diagnosed with BTAI from January 1999 to January 2020 was performed. Data were collected from electronic/digitalized medical history records. RESULTS: Forty-six patients were included [median age 42.4 years (16–84 years), 71.7% males]. The predominant cause of BTAI was car accidents (54.5%, n  = 24) and all patients presented with concomitant injuries (93% bone fractures, 77.8% abdominal and 62.2% pelvic injuries). Over 70% presented grade III or IV BTAI. Urgent repair was performed in 73.8% of patients ( n  = 31), with a median of 2.75 h between admission and repair. Thoracic endovascular repair (TEVAR) was performed in 87% ( n  = 49), open surgery (OS) in 10.9% ( n  = 5) and conservative management in 2.1% ( n  = 1). Technical success was 82.6% (92.1% TEVAR, 79% OS). In-hospital mortality was 19.5% (17.5% TEVAR, 40% OS). Of these, 3 died from aortic-related causes. Seven (15.2%) required an early vascular reintervention. The median follow-up was 34 months (1–220 months), with 19% of early survivors having a follow-up of >10 years. Only 1 vascular reintervention was necessary during follow-up: secondary TEVAR due to acute graft thrombosis. Of the patients who survived the initial event, 6.7% died during follow-up, none from aortic-related causes. CONCLUSIONS: Even with all the described shortcomings, in our experience TEVAR for BTAI proved to be feasible and effective, with few complications and stable aortic reconstruction at mid-term follow-up. With the current technical expertise and wide availability of a variety of devices, it should be pursued as a first-line therapy in these challenging scenarios.